Life Skills Education Program In Improving Student Independence - Rohmah, Liatul; Tanzeh, Ahmad; Qomar, Mujamil; Zaenul Fitri, Agus (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Vocational High School (SMK) as a level of formal education that provides special skills in preparing graduates to be ready to work and well-developed independence. The graduates produced are in the form of a ready-to-use workforce, in the sense that they can directly work as expected and needed by society, especially the people of the Business World, the Industrial World and the World of Work (DUDIKA). The manpower needed is skilled labor as quality human resources according to their competence and expertise and has high competitiveness.The research method used in this study uses a qualitative method with a cross-site phenomonological approach. Data collection techniques are participant observation, indepth interviews and documentation. The data analysis techniques used were 1) single case data analysis, 2) cross-site analysis. The research results show that:The Lifeskills Education Program in Enhancing Student Independence in the two educational institutions is: Adapting the curriculum to the competencies needed by the world of work; Determination of theoretical and practical learning activities according to the expertise program; Teachers are teachers who are professionals in their field; Determining strategies for conducting training, building partnerships, knowledge and technology innovation to produce professional graduates; Development of life skill programs, Procurement of written and practical exams (competence test), Implementation of life skills education.